The properties of plasma-liquid system with one liquid electrode - Nedybaliuk, O.A.; Solomenko, O.V.; Chernyak, V.Ya.; Martysh, E.V.; Fedirchyk, I.I.; Prysiazhnevych, I.V. (Вопросы атомной науки и техники, 2013)
The results of investigations are presented for a rotational gliding arc with liquid electrode. Emission spectra of rotational gliding arc discharge with liquid electrode were investigated. The discharge voltage as a function of airflow rate were measured. Electronic Te*, vibrational Tv* and rotational Tr* temperature were determined. Distribution of temperature along the plasma torch was studied. Представлено результати дослідження обертової ковзної дуги з рідким електродом. Досліджено спектри випромінювання плазми обертової ковзної дуги з рідким електродом. Виміряно залежність напруги розряду від величини потоку повітря. Визначено електронні Te*, коливні Tv* та обертові Tr* температури. Досліджено розподіл цих температур вздовж плазмового факела. Представлены результаты исследования вращательной скользящей дуги с жидким электродом. Исследованы спектры излучения плазмы вращательной скользящей дуги с жидким электродом. Измерена зависимость напряжения рaзряда от величины потока воздуха. Определены электронные Te*, колебательные Tv* и вращательные Tr* температуры. Исследовано раcпределение температур вдоль плазменного факела.